Sensitivity Analysis of Range Dynamics Models (SARDM): Quantifying the influence of parameter uncertainty on forecasts of extinction risk from global change. (September 2016) - Fordham, Damien A.; Haythorne, Sean; Brook, Barry W.
Abstract: Spatially explicit demographic models are increasingly being used to forecast the effect of global change on the range dynamics of species. These models are typically complex, with the structure and parameter values often estimated with considerable uncertainty. If not properly accounted, this can lead to bias or false precision in projections of changes to species range dynamics and extinction risk. Here we present a new open-source freeware tool, "Sensitivity Analysis of Range Dynamics Models" (SARDM) that provides an all-in-one approach for: (i) determining the implications of integrating complex and often uncertain information into spatially explicit demographic models compiled in RAMAS GIS, and (ii) identifying and ranking the relative importance of different sources of parameter uncertainty. The sensitivity and uncertainty analysis techniques built into SARDM will facilitate ecologists and conservation scientists in better establishing confidence in forecasts of range movement and abundance. Highlights: Developed a tool for characterizing model uncertainty and parameter sensitivity. Identifies which model parameters influence predictions of extinction risk. Allows parameter uncertainty to propagate through to ecological forecasts. Provides improved confidence in measures used to protect biodiversity.